Restorative Therapies after Stroke: Drugs, Devices and Robotics - Srivastava, MV Padma (Annals of the National Academy of Medical Sciences (India), 2017)
Restorative therapies aim to improve outcome and function by promoting plasticity within a therapeutic time window between days to weeks to years. In this article, the mechanisms by which cell-based, pharmacological and robotic treatments stimulate endogenous brain remodelling after stroke, particularly neurogenesis, axonal plasticity and white-matter integrity are described with a brief outline of the potential of neuroimaging (fMRI) techniques. Stem cells aid stroke recovery via mechanisms depending on the type of cells used. Transplanted embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), and neural stem cells (NSCs) can replace the missing brain cells in the Infarcted area, while adult stem cells, such as mesenchymal stem cells or multipotent stromal cells (MSCs) and MNCs, provide trophic support to enhance self-repair systems such as endogenous neurogenesis. Most preclinical studies of stem cell therapy for stroke have emphasized the need to enhance self-repair systems rather than to replace lost cells, regardless of the type of cells used. Noninvasive brain stimulation (NIBS) provides a valuable tool for interventional neurophysiology by modulating brain activity in a speciﬁc distributed, cortico-subcortical network. The two most commonly used techniques for noninvasive brain stimulation are transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS). The article also discusses the potential role and current evidence for the use of pharmacological therapy, robotics and speciﬁc forms of physiotherapy regimes in optimizing stroke recovery. Neurorestoration is a concept that has been proven emphatically in several experimental models and clinical studies of stroke. Elucidating the underlying mechanisms of cell-based, pharmacological and rehabilitative therapies is of primary interest and crucial for translation of treatments to clinical use. The knowledge must provide an impetus for the development of superior, advanced and cost effective neuro restorative interventions that will enhance stroke recovery.
Keywords: Cerebral stroke; stroke therapy; functional neuroimaging